(3YfhGf GdfaGSI aj TQM OjhGf GdMeGSIs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd bQBfkG YQHjkG ZjQ Pj YhL, hLYd dg ef GdcdGe GdYQHj eYGQL PhGJ OQL CeG HYO, agPG TQM Ydi GdMeGSI SejJg HYfhGf GdfaGSI, jSJgOj Ph GdfaS s
(3BNQgG (B:s
(3JfJgj HbGajI GdSjf ef HGH GdcHQ s
(3GdMeGSI dCHj JeGes
(3hgPG GdLRA gh GdfUa GdChds
(3hjMJhj Ydi CHhGHs
(3hgh eQJH Ydi GdbhGaj OGNd cd HGHs
(3UaMI GdYfhGf ePgHI s
(3HChdgG agQS HCHhGH GdcJGH s
Keywords: (3GdCOHs